2005
DOI: 10.1021/ja043431g
|View full text |Cite
|
Sign up to set email alerts
|

Functional One-Dimensional Lipid Bilayers on Carbon Nanotube Templates

Abstract: Use of biological machines and environments in novel bioinorganic nanostructures is critical for development of new types of biosensors, bio-NEMS devices, and functional materials. Lipid bilayers that mimic a cell membrane have already played an important role in such applications. We present supported lipid bilayers that spontaneously assemble in a continuous nanoshell around a template of a carbon nanotube wrapped with hydrophilic polymer cushion layers. We demonstrate that such 1-D lipid membranes are fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 55 publications
2
59
1
Order By: Relevance
“…The self-assembly of lipid molecules into a fluidic 1D nanostructure on a CNT template was reported, and the lipid lateral fluidity was tested by tuning the diameter of the CNTs (Figure 3a). 37 For support of the hydrophilic head groups of the lipid bilayer, the CNTs were wrapped with polyelectrolytes in a layer-by-layer manner. The assembled polyelectrolytes electrostatically stabilized the lipid bilayer in a 1D configuration and allowed control of the diameter of the structure.…”
Section: Lipid-1d-nanostructure Hybridsmentioning
confidence: 99%
“…The self-assembly of lipid molecules into a fluidic 1D nanostructure on a CNT template was reported, and the lipid lateral fluidity was tested by tuning the diameter of the CNTs (Figure 3a). 37 For support of the hydrophilic head groups of the lipid bilayer, the CNTs were wrapped with polyelectrolytes in a layer-by-layer manner. The assembled polyelectrolytes electrostatically stabilized the lipid bilayer in a 1D configuration and allowed control of the diameter of the structure.…”
Section: Lipid-1d-nanostructure Hybridsmentioning
confidence: 99%
“…bilayer counterbalances the elastic energy of the bilayer deformation. [ 87 ] Our group demonstrated that lipid vesicle fusion on CNTs modifi ed with several hydrophilic polymer layers produces a continuous lipid bilayer shell (1D bilayer) around the nanotube [ 88 ] ( Figure 6 a,c ) and subsequently showed that a similar lipid bilayer shell could assemble around a hydrophilic polysilicon nanowire without any polymer cushion layer [ 87 ] (Figure 6b,e ). Lipid bilayer shells can also assemble on a larger nanowire structures, such as SnO2 nanowire waveguides [ 89 ] (Figure 6d ).…”
Section: Cell and Tissue Interfacesmentioning
confidence: 97%
“…Our group measured in-plane diffusion coeffi cients of ca. 3 × 10 − 11 cm 2 s − 1 for lipid bilayers adsorbed on polymer layer-modifi ed CNTs [ 88 ] using fl uorescence recovery after photobleaching (FRAP) experiments. This value is almost two orders of magnitude slower than the values observed for planar supported lipid bilayers on polymer substrates, [ 92 ] which could refl ect a large degree of bilayer imperfection on these substrates as well as strong charge-charge interactions of lipid head groups with the polymer.…”
Section: Cell and Tissue Interfacesmentioning
confidence: 99%
“…Furthermore, the research and application of CNTs produces continuous advances and novel approaches in the design of electrochemical sensors and biosensors [10]. CNTs have emerged as attractive candidates in diverse nanotechnological applications, such as fillers in polymer matrixes, which can improve the electrical and mechanical properties of the polymer [11,12].…”
Section: Introductionmentioning
confidence: 99%